Manajemen Pendidikan Melalui Peningkatan Kompetensi Guru - Ghoiri Ahmat (Universitas Islam Kadiri, 2020)
This study uses a qualitative method. The study was conducted at 6 Kediri MTsN, from February to May 2019. The subjects of the study were the Head of the Kediri 6 MTsN School. The informants in the study were Deputy Head of Curriculum, Teachers and Students. Data collection techniques by means of interviews, observation and documentation. The validity of the data uses data triangulation and source triangulation. Data analysis uses interactive methods, data collection, data presentation, data reduction and conclusion drawing. The results of the study show that (1) Management of Education Quality Improvement through Competency Improvement of Teachers in the Academic Year at Kediri 6 MTsN 2018/2019 academic year is carried out through the stages of planning, organizing, implementing, recruitment, training, compensation and evaluation processes, (2) Increased Management Barriers The Quality of Education through Teacher Competency Improvement in Kediri MTsN 6 in the 2018/2019 school year is on human resource management, development of Teacher training and the high level of complexity of Teacher's work, (3) Management Solution for Education Quality Improvement through Teacher Competency Improvement in Kediri 6 MTsN The 2018/2019 school year is by increasing support from outside and collaborating with various parties in improving the quality of education and providing training to educators.